(untitled) (Biuletyn Kryminologiczny, 2021)
Przestępczość jest złożonym zjawiskiem społecznym, istotnym dla całego społeczeństwa. Dlatego też od lat podejmuje się działania mające na celu poszerzenie wiedzy o czynnikach odpowiedzialnych za zachowania polegające na przekraczaniu norm przez uczestników życia społecznego oraz poszukiwaniu takich czynników, które odgrywają rolę pozytywną (chroniącą). W zależności od wiodącego nurtu badawczego, czynników takich poszukiwano w cechach indywidualnych jednostki lub też w środowisku zewnętrznym (rodzina, środowisko lokalne). Wiele badań poświęcono również weryfkowaniu zewnętrznych oznak czy genetycznych odchyleń wskazujących na predyspozycje do zachowań przestępczych. Nie bez znaczenia wydają się także czynniki neurobiologiczne, a w szczególności rozpowszechnienie zaburzeń psychicznych w populacji. Aktualnie trendy w prowadzonych badaniach czerpią z dorobku wielu dziedzin. Podkreśla się jednak, że każde zachowanie człowieka determinowane jest nie tylko przez jego osobowość, ale również przez środowisko, w jakim się znajduje. Problematyka przestępczości jest tym ważniejsza, gdy zjawisko to dotyczy dzieci i młodzieży. Analiza dostępnych danych statystycznych dotyczących czynów karalnych popełnianych przez nieletnich wskazuje, że kwestia ta stanowi istotny problem społeczny. W 2015 roku w statystyce sądowej odnotowano ponad 12 tys. czynów karalnych popełnianych przez nieletnich sprawców oraz ponad 14 tys. orzeczeń sądowych w sprawach nieletnich w związku z demoralizacją. Ponadto, nie bez znaczenia wydaje się obniżający się wiek młodzieży wchodzącej „na drogę przestępczą”. Celem badań była ocena rozpowszechnienia oraz analiza uwarunkowań tzw. „czynników ryzyka” w etiologii czynów przestępczych. Aby przeprowadzić analizę uwarunkowań przeprowadzono badania samoopisowe młodzieży, wywiady oraz testy psychologiczne, a uzyskany szeroki materiał empiryczny pozwolił na wychwycenie pewnych cech charakterystycznych oraz różnic pomiędzy młodzieżą, która przyznała się do popełnienia przestępstwa oraz tymi, którzy takich doświadczeń nie mieli. Opracowanie składa się z dwóch części. Pierwsza stanowi teoretyczne uzasadnienie podjętej tematyki badań. Druga natomiast ma charakter empiryczny i obejmuje opis metody, a także uzyskane wyniki badań wraz z ich omówieniem i interpretacją. Badanie przeprowadzone zostało na grupie uczniów w wieku 15-19 lat, przy wykorzystaniu trzech metod badawczych (kwestionariusza samoopisowego, testów psychologicznych oraz wywiadu). Crime is a multidimensional social phenomenon, important for the whole society For years, researchers have been conducting research to increase knowledge about the factors respon- sible for criminal behavior and to look for such factors that play a positive (protective) role. Depending on the leading research trend, such factors were sought in the individual’s characte- ristics or in the external environment (family, local environment). Many studies have also been devoted to verifying external signs and genetic deviations indicating predisposition to criminal behavior. Some scientists also point to neurobiological factors, in particular the prevalence of mental disorders in the population. Currently, the trends of research are taken from many ﬁelds of science. It is emphasized, however, that every human behavior is determined not only by his personality, but also by the environment in which he is located. The issue of crime is more im- portant when this phenomenon applies to children and young people. The analysis of available statistical data on criminal oﬀenses committed by minors shows that this issue is a signiﬁcant social problem. In 2015, in court statistics there were over 12 000 criminal oﬀenses committed by juvenile oﬀenders and over 14 000 court judgments on demoralization of minors. Furthermore it stresses that the age of young people commitng crimes signiﬁcantly decreased. The aim of the study was the evaluation of prevalence and analysis of determinants of „risk fac- tors” in the etiology of criminal acts. Risk factors are deﬁned as individual personal properties, environmental characteristics and mutual interactions between them. In the statistical sense, risk factors are properties that coexist with abnormal behavior or precede its formation. Based on knowledge about risk factors, we can try to estimate the occurrence of certain negative phe- nomena, including for example committing oﬀenses by young people. It should be emphasized that the emergence of risk factors does not necessarily lead to negative consequences, but they increase the risk of their occurrence. The study used a self-report questionnaire, psychological tests and an interview. The obtained empirical material allowed to capture certain characteristics and diﬀerences between the youth who admitted committing the crime and those who did not have such experiences. The work consists of two parts. The ﬁrst is a theoretical justiﬁcation of the subject matter of research. The second is empirical and includes a description of the method and the results of research and their discussion and interpretation. The survey was conducted on a group of students aged 15-19 years, using three methods (survey research using psychological tests, self-study report and the interview). Thus obtained results allowed to show the current trend of youth crime related to gender and the prevalence of risk behaviors (drinking strong alcohol or drug use). Analyzes were also a number of environmental factors, and on the basis of indicators developed “the goodness of the local environment.” Analyses showed that there were features diﬀerentiating the family of the young people. The collected research material allowed to show the diﬀerences between the two groups of young people and to isolate psychosocial risk factors which youth crime.